Students’ Algebraic Proficiency from the Perspective of Symbol Sense - Jupri, Al; Sispiyati, Ririn (Indonesian Journal of Science and Technology, 2020)
Algebraic proficiency, including procedural fluency and conceptual understanding, is widely discussed worldwide. Algebraic proficiency refers largely to proficiency in symbolic representations which can be investigated through a framework of symbol sense. This research, therefore, aims to analyze students’ algebraic proficiency in terms of symbol sense. We set up a pilot study, involving 22 Indonesian mathematics education students (18-19 year old), in the form of two weeks teaching that combine a conventional approach and the use of a camera calculator in the learning and teaching of quadratic and related equations. The results showed that more than half number of students lacks of symbol sense in the sense that they tend to use procedural strategies rather than symbol sense strategies in solving equations. From the perspective of symbol sense, we concluded that the students acquired more on procedural fluency than on conceptual understanding.